(untitled) (Global Journal of Science Frontier Research, 2019)
The ’Computational Unified Field Theory’ (CUFT)’ New Universe Introduction-Twenty-first century Physics is undergoing a major "Paradigmatic-Shift"-i.e., from the old "Material-Causal" Paradigm underlying both Relativity Theory (RT) and Quantum Mechanics (QM) towards the new ’A-Causal Computation’ (ACC) Paradigm of the ’CUFT’. This basic ’Paradigmatic Shift’ alters Science’s very fundamental assumptions and conception of the reality of the physical universe -i.e., its origination-sustenance-evolution-and transcendence based on the discovery of a singular (higher-ordered) ’Universal Consciousness Principle’ which simultaneously computes every exhaustive spatial pixel in the universe at every minimal timepoint (e.g., "c 2 /h = 1.45 -42 sec’!); Hence, the scope and purpose of the current article is to delineate the basic ’Paradigmatic Shift brought about by the CUFT’s new ’ACC’ outline the major breakthrough advancement in 21 st century Theoretical Physics brought about by this new CUFT’s ’A-Causal Computation’ (ACC) Paradigm, explicate the experimental means for validating this new ACC as a satisfactory "Theory of Everything" (TOE), and describe the new (exciting) emerging picture of the entire physical universe as a "transient-phenomenal" manifestation of this singular ’Universal Consciousness Reality’...